The Influence of World Gold Prices, World Oil Prices, and US Dollar (USD) Exchange Rate on the Indonesian Composite Index (IHSG) Period 2013-2022 - Amthy Suraya; Pratama Fauzi Nurdiantoro (Formosa Journal of Sustainable Research, 2023)
This study intends to decide the impact of world gold costs, world oil costs, and the US dollar (USD) conversion scale on the Indonesian Composite Record (IHSG) during the period 2013-2022. The strategy utilized in this study is the Quantitative Clear Technique utilizing auxiliary information from finance yippee, list mundi, BPS, and IDX for the years 2013-2022. The information examination strategy utilized in this exploration incorporates exemplary supposition tests, different direct relapse investigation, speculation testing (T-test and F-test), and coefficient of assurance (R2) test. The aftereffects of this exploration demonstrate that the factors of world gold costs and world oil costs don't altogether influence the IHSG during the period 2013-2022. The USD swapping scale variable essentially affects the IHSG during the period 2013-2022. In addition, the IHSG is significantly influenced by the global oil and gold prices, as well as the USD exchange rate, from 2013 to 2022. The results of the coefficient of determination (R2) test show that the IHSG can be affected by world gold prices, world oil prices, and the USD exchange rate as a whole by 64.1%